The Influence of Parents' Income, Family Environment, Learning Motivation on Interest In Following PPG (Program Profesi Guru) - Jessica Chintyawati (Economic Education Analysis Journal, 2023)
Interest is a person's interest because of a feeling of liking for a thing or activity related to a particular object. In this case is the interest to take part in PPG. This study aims to determine the effect of parental income, family environment, and learning motivation on interest in participating in PPG. This type of research is quantitative research. The population in this study were 259 students majoring in Economic Education at UNNES class of 2017. The sample in this study was 157 students. The sampling technique used is stratified random sampling technique. Methods of data collection using a questionnaire. The results showed that (1) Parents' income had a positive effect on interest in participating in PPG; (2) Family environment had no positive and significant effect on interest in participating in PPG; (3) Learning motivation had a positive effect on interest in participating in PPG; (4) Parents' income, family environment, and learning motivation simultaneously has an effect of 27.9% on students' interest in participating in PPG.